Superior gene transfer into solid tumour cells than into human mobilised peripheral blood progenitor cells using helpervirus-free adeno-associated viral vector stocks - Veldwijk, Marlon Romano; Schiedlmeier, Bernhard; Kleinschmidt, Jürgen; Zeller, W. Jens; Frühauf, Stefan (European journal of cancer, 1999)
Autologous peripheral blood progenitor cell (PBPC) grafts can be contaminated with tumour cells that potentially give rise to relapse following myeloablative therapy and PBPC transplantation. Adeno-associated virus (AAV)-based vectors produced by a new adenovirus-free technique are a gene delivery system which may be applicable for tumour cell purging. To test for the host range of these vectors, solid tumours of clinical relevance and normal CD34+ PBPC were selected as target cells for an AAV-vector, encoding the green-fluorescent protein (GFP) as the indicator gene. At a multiplicity of infection (MOI) of 100: 79.94%±14.36% (mean±SEM) of the connective tissue sarcoma cell line (HS-1) and 64.84%±6.91% of the cervical carcinoma cell line cells (HeLa-RC) expressed GFP while the other cell lines tested (1 ovarian tumour, 1 germ cell tumour, 1 osteosarcoma, 2 small cell lung cancer) ranged between 2.82% and 11.94%. Optimising the transduction protocol by use of higher MOIs of up to 500 and by pretreatment with the tyrosine kinase inhibitor, genistein, resulted in up to 95.97% and 94.10% green-fluorescent HS-1 and HeLa-RC cells, respectively. In contrast, only 1.39%±0.51% of the normal haematopoietic CD34+ progenitor cells expressed GFP at a MOI of 100. The differential infectivity between HS-1 and CD34+ cells was maintained after tumour cell spiking in leucapheresis products. Our observations suggest that AAV-based vectors may prove useful for purging of autologous PBPC grafts from solid tumour cells.
Gesehen am 20.01.2022